Thermomechanical model for evaluation of the superelastic response of NiTi shape memory alloys under dynamic conditions - Soul, Hugo Ramon (2013)
The development of a 1-D thermomechanical model for simulating the response of uniaxial superelastic NiTi elements is described. The formulation of the model includes consideration of the dependence of the critical stresses for forward and reverse transformation on the temperature, the occurrence of strain rate effects due to self-heating / cooling associated with the latent heat of the stress induced martensitic transformation, the localized character of the stress induced transformation in superleastic NiTi wires and ribbons, the possibility of nucleation events both during the forward and reverse transformations and the occurrence of nonrecoverable residual strains. Numerical simulations allowed rationalizing different features commonly observed in experiments and their dependence with strain rate and environment conditions. Comparisons of numerical results with experimental cycles obtained in the present work and also with data published in the literature indicate the potentiality of the developed model as design tool for simulating the response of superelastic materials subjected to realistic service conditions.